Adult Drug and Alcohol Problems, Children's Needs, Second Edition : an Interdisciplinary Training Resource for Professionals - with Practice and Assessment Tools, Exercises and Pro Formas. - Barlow, Joy (Jessica Kingsley Publishers, 2016)
Parental drug use can cause serious harm to children. Adult Drug and Alcohol Problems, Children's Needs supports practitioners in their work with families where parental drug use leads to concerns about children's welfare. The training resource contains: summaries of the key messages for practitioners, tools and tips to support effective practice, training and development activities, practice examples from around the UK. This second edition has an increased focus on alcohol misuse and reflects recent changes to both policy and practice. The book will be useful for all individuals and agencies involved with families where parents are struggling with substance abuse, including children's social workers, substance misuse workers, primary care and school staff, criminal justice agencies, obstetric and paediatric teams, substitute carers and a range of voluntary and community services.